Pharmacokinetics of Pimobendan and Its Metabolite O-Desmethyl-Pimobendan Following Rectal Administration to Healthy Dogs - Her, Jiwoong; Kuo, Kendon W.; Winter, Randolph L.; Cruz-Espindola, Crisanta; Bacek, Lenore M.; Boothe, Dawn M. (Frontiers in Veterinary Science, 2020)
Objective: This study describes the pharmacokinetics of parent pimobendan (PIM) and its active metabolite, o-desmethyl-pimobendan (ODMP), after oral and rectal administration of pimobendan to healthy dogs. Animals: A total of eight healthy privately owned dogs were used in this study. Procedures: The dogs received a single dose (0.5 mg/kg) of a commercially available pimobendan tablet per os (PO). Twelve blood samples were collected over a 12-h period for pharmacokinetic analysis. After a 24-h washout period, the dogs received the same dose of pimobendan solution per rectum (PR), and samples were obtained at the same time for analysis. Results: For PIM, PO vs. PR, respectively, the mean maximum plasma concentration (Cmax, ng/ml) was 49.1 ± 28.7 vs. 10.1 ± 2, the time to reach a maximum concentration (Tmax, h) was 2.1 ± 0.9 vs. 1 ± 0.4, the disappearance half-life (t1/2, h) was 1.8 ± 0.8 vs. 2.2 ± 0.6, and the area under the concentration–time curve (AUC, ng*h/ml) was 148.4 ± 71.6 vs. 31.1 ± 11.9, with relative bioavailability (F, %) of 25 ± 8. For ODMP, PO vs. PR, respectively, Cmax was 30.9 ± 10.4 vs. 8.8 ± 4.8, Tmax was 3.2 ± 1.6 vs. 1.7 ± 1.1, and t1/2 was 5.0 ± 2.7 vs. 8.3 ± 4.8, with AUC of 167.8 ± 36.2 vs. 50.1 ± 19.2 and F of 28 ± 6. The differences between PO and PR were significant (P < 0.03) for AUC and Cmax for both PIM and ODMP. Conclusions and Clinical Relevance: The pharmacokinetics of PIM and ODMP were described following PO and PR administration. The findings suggest that pimobendan PR might achieve effective concentrations and, as such, warrant future studies of clinical effectiveness in treating dogs with congestive heart failure and which are unable to receive medication PO.